Management of patients with severe Epstein syndrome: Review of four patients who received living‐donor renal transplantation. Issue 4 (27th March 2019) - Hashimoto, Junya; Hamasaki, Yuko; Takahashi, Yusuke; Kubota, Mai; Yanagisawa, Taketo; Itabashi, Yoshihiro; Muramatsu, Masaki; Kawamura, Takeshi; Kumagai, Naonori; Ohwada, Yoko; Sakai, Ken; Shishido, Seiichiro
ABSTRACT: Aim: Epstein syndrome is a hereditary disease characterized by macrothrombocytopaenia and progressive nephritis. The abnormality of the MYH9 gene has a strong relationship to the severity of the disease. Severe Epstein syndrome progresses to end‐stage renal disease rapidly after adolescence. There is no established therapy. We sought to clarify appropriate management of Epstein syndrome nephropathy. Methods: Epstein syndrome patients who underwent renal transplantation at our institution between March 2009 and March 2017 were enrolled. Epstein syndrome was diagnosed based on clinical features and genetic testing. Patient medical records were reviewed retrospectively. Results: Four male patients with Epstein syndrome, all with severe MYH9 gene mutations (p.R702C in three and p.S96L in one), were enrolled. Despite treatment with renin–angiotensin system blockers, nephropathy was refractory and progressed rapidly, and the patients required dialysis or renal transplantation after adolescence. Early preparation for treatment based on early and accurate diagnosis of Epstein syndrome enabled two patients to undergo pre‐emptive renal transplantation. For these patients, we kept the platelet count above 100 × 10 9 /L until day 7 after renal transplantation with platelet transfusions for macrothrombocytopaenia, and no postoperative bleeding episodes occurred. Conclusion: Epstein syndrome nephropathy due to a severe MYH9 gene mutation can be refractory and progress rapidly; therefore, early and accurate diagnosis is important for safer therapeutic options including pre‐emptive renal transplantation. By keeping the platelet count above 100 × 10 9 /L during the perioperative period, renal transplantation can be a safe treatment option for severe Epstein syndrome nephropathy. Summary at a Glance: This article describes successful renal transplantation in four cases of Epstein syndrome nephropathy due to severe MYH9 gene mutation. Epstein syndrome is characterized by thrombocytopaenia and progressive renal impairment. The four cases ranged in age from 15 to 35 years old.